Retratar la reforma carcelaria: Estado, política y fotografías durante el peronismo clásico - Jeremías Silva (Centre de Recherches sur les Mondes Américains, 2021)
The aim of this work is to examine a photographic album edited by the Direccion General de Institutos Penales of Argentina during the direction of Roberto Pettinato. This visual document contains 27 photographs of the visit made in October 1948 by the Minister of Justice and Public Instruction of the Peronist government, Dr. Belisario Gache Pirán, to the National Penitentiary. In this way, we will investigate the images of the album to understand the meanings of prison reform and illuminate central aspects of the state transformations that occurred during classical Peronism.